2020
DOI: 10.1111/ajo.13242
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ultrasound findings and laparoscopy in prediction of deep infiltrating endometriosis (DIE)

Abstract: Endometriosis affects 10-15% of women and can result in significant deterioration in quality of life. 1-4 Deep infiltrating endometriosis (DIE) is the term used when endometrial implants, fibrosis and muscular hyperplasia are present below the peritoneum (>5 mm) and involve, in descending order of frequency, the uterosacral ligaments, the rectosigmoid colon, the vagina and the bladder. 3,5-7 It can alter the normal pelvic anatomy and be associated with significant adhesions in the pelvis which may make surgical Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
(22 reference statements)
3
0
0
1
Order By: Relevance
“…Recently the role of USG as a non-invasive instrument in endometriosis has shown promising results [14]. The present work demonstrates high concordance between TV scan and laparoscopic ndings as per #Enzian classi cation.…”
Section: Discussionsupporting
confidence: 70%
“…Recently the role of USG as a non-invasive instrument in endometriosis has shown promising results [14]. The present work demonstrates high concordance between TV scan and laparoscopic ndings as per #Enzian classi cation.…”
Section: Discussionsupporting
confidence: 70%
“…TVS was found to detect more single OEs than laparoscopy, while the latter found more multiple OEs than the former. According to the present findings, the most common extraovarian sites for DIE, found on both TVS and laparoscopy, were the uterosacral ligament (USL) in PPC and the bladder base in APC; these findings are comparable to those of previous studies (19).…”
Section: Discussionsupporting
confidence: 91%
“…Our sensitivity and specificity were high at 82.5% and 98.4% respectively similar to previously published results [9,16,33,35]. Other investigators reported lower sensitivity and specificity [28,31,32,36,37]. In our series, the torus was almost always affected with bilateral USL involvement with 95.7% of bilateral uterosacral DIE showing torus plaques.…”
Section: Discussionsupporting
confidence: 90%